THE CRISIS OF TRUTH AND THE CALLING OF THE CHURCH: THE RELEVANCE OF FRANCIS SCHAEFFER'S ANALYSIS IN THE POST-TRUTH ERA - Elis; situmorang, Alexander (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract: The contemporary world is experiencing a crisis of truth, characterized by the dominance of emotions, personal beliefs, and ideological narratives over objective facts and moral absolutes. This phenomenon, known as the post-truth era, has significant ethical, social, and theological implications, particularly for the Christian Church. Francis Schaeffer, a prophetic evangelical thinker of the twentieth century, provided a penetrating analysis of Western culture's departure from absolute truth in his seminal work, "The God Who Is There." Schaeffer warned that the rejection of transcendent, divinely revealed truth would inevitably lead to moral relativism, societal disintegration, and the collapse of meaningful communication. This paper critically examines Schaeffer’s analysis in light of contemporary post-truth dynamics and explores the Church's theological and prophetic responsibility in responding to this cultural crisis. The study argues that Schaeffer’s call for the Church to reclaim its commitment to biblical truth, cultivate intellectual discernment, and courageously confront cultural falsehood remains profoundly relevant today. By engaging both theology and public discourse, the Church is challenged to be a countercultural community that bears witness to the truth of the Gospel amidst a society increasingly indifferent to facts and moral objectivity.